Peningkatan Kapasitas Pemasaran Digital UMKM melalui Pelatihan E-Commerce dan Branding Produk di Desa Sungai Rebo - Yunita; Elly Rosana; Thirtawati; Henny Malini; Trissa Silvian; Khosy Khoirunnisa (Universitas Muhammadiyah Malang, 2026)
Purpose – This community service program aims to enhance the capacity of MSME actors in Sungai Rebo Village in utilizing digital marketing through e-commerce platforms to address limited market access, low digital literacy, and inadequate skills in creating promotional content. The program is designed to expand marketing reach, increase the added value of local products, and strengthen the village’s economic independence. Design/methodology/approach – The activities were implemented through five stages: socialization, training on digital marketing and content creation, technology implementation through hands-on practice in creating e-commerce accounts, continuous mentoring, and evaluation of competency improvement using pretest and posttest assessments. Findings – The results indicate a significant increase in participants’ knowledge and skills in managing online stores, uploading products, and utilizing digital promotion features. The paired sample t-test confirmed a meaningful difference between pretest and posttest scores, demonstrating the effectiveness of the training. Participants successfully created Shopee store accounts and began developing their digital product showcases. Originality/value –This program provides a tangible contribution to supporting digital transformation among village-based MSMEs through practical approaches and direct mentoring. Its novelty lies in integrating e-commerce training with simple promotional content creation techniques that are accessible to rural MSMEs. The program aligns with several SDGs, including poverty reduction, economic growth, and innovation.